2017
DOI: 10.1158/1538-7445.am2017-3151
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3151: Loss of Axin1 drives acquired resistance to WNT pathway blockade in colorectal cancer cells carrying RSPO3 fusions

Abstract: In colorectal cancer (CRC), WNT pathway activation by genetic rearrangements of RSPO3 is emerging as a promising target. However, its low prevalence severely limits availability of preclinical models for in-depth characterization. Using a pipeline designed to suppress stroma-derived signal, we find that RSPO3 “outlier” expression in CRC samples highlights translocation and fusion transcript expression. Outlier search in 151 CRC cell lines identified VACO6 and SNU1411cells as carriers of, respectively, a canoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…The growth of APC mutant organoids does not rely on Wnt or R-spondin1 5. Our organoid models offer a unique opportunity to study this process, since pre-existing cell models, including the two known RSPO fusion CRC cell lines, VACO6 and SNU-1411, do not require Wnt as part of their culture conditions 27 28. Therefore, we performed single-cell RNAseq analysis on the two RSPO fusion tumour-normal paired organoids (H011 and H019), with and without differentiation via Wnt withdrawal (online supplementary figure 1 and online supplementary table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The growth of APC mutant organoids does not rely on Wnt or R-spondin1 5. Our organoid models offer a unique opportunity to study this process, since pre-existing cell models, including the two known RSPO fusion CRC cell lines, VACO6 and SNU-1411, do not require Wnt as part of their culture conditions 27 28. Therefore, we performed single-cell RNAseq analysis on the two RSPO fusion tumour-normal paired organoids (H011 and H019), with and without differentiation via Wnt withdrawal (online supplementary figure 1 and online supplementary table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic resistance to the PORCN inhibitor has been observed in some pancreatic cancer cell lines harboring inactivating mutations of RNF43, although the resistance mechanism remains unclear [8]. It was also reported that long-term exposure to a PORCN inhibitor in vitro selected for a AXIN1-mutant clone in a RSPO3-translocated colorectal cancer cell line and the AXIN1 mutation drove acquired resistance to the PORCN inhibitor [20]. Moreover, on-target adverse effects of Wnt pathway blockade by PORCN inhibitors, including bone loss and dysgeusia, were observed in a preclinical study and clinical trials [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, these cells developed resistance to LGK974 within 3 months when cultured with a sublethal concentration of LGK974. Exome sequencing of the resistant VACO6 clone found truncating mutations in AXIN1 that are absent in the parental cell line (Picco et al, 2017). Interestingly, these truncating mutations have been reported in the Catalogue of Somatic Mutations in Cancer database as cancer-related somatic variants.…”
mentioning
confidence: 98%